Board-level worker representation - Gregorič, Aleksandra (Global Labor Organization (GLO), 2022)
This chapter reviews the literature on board-level worker representation (BLWR). BLWR refers to workers' legally sanctioned rights to take part in the decisions of their employers' board of directors as full or consultative members, regardless of their underlying equity investments. It provides information about the incidence of BLWR across countries, and the factors that likely contributed to the establishment of this mechanism of employee voice. It reviews theory on the positive and negative impacts of BLWR for workers and firms, summarizes the related empirical evidence, and concludes by pointing to the open gaps as avenues for future research.
10419/261793
Keywords: Graue Literatur; board-level worker representation; theoretical and empirical review; cross-country evidence; firm performance; boardroom